Superior Mesenteric Artery Syndrome: A Potentially Fatal but Reversible Gastrointestinal Manifestation of Systemic Sclerosis - Choon-Guan Chua; Gervais Khin-Lin Wansaicheong; Wee-Chian Lim; Bernard Yu-Hor Thong (Case Reports in Rheumatology)
Superior mesenteric artery syndrome (SMAS) is a rare gastrointestinal disorder characterised by vascular compression of the third part of the duodenum, in the angle between the superior mesenteric artery (SMA) and the abdominal aorta. It presents as an uncommon cause of upper gastrointestinal obstruction. In patients with systemic sclerosis (SSc), gastrointestinal involvement may result in oesophageal dysmotility, gastroesophageal reflux disease (GERD), gastroparesis, small intestinal bacterial overgrowth (SIBO), chronic intestinal pseudoobstruction (CIPO), and fecal incontinence. Malnutrition may thus result in weight loss and reduced mesenteric and retroperitoneal adipose tissue, decreasing the angle between the SMA and aorta causing SMAS. Enteral or parenteral feeding can potentially reverse SMAS in SSc. We report a case of SMAS in an elderly female with SSc and concurrent gastrointestinal involvement, and discuss the important management considerations and potential adverse outcomes when untreated.